Press performance amid threats of terror: Exploring reporting thresholds and criticism in elite coverage of an Identity Cards Bill. (October 2019) - Matthews, Julian; Cameron, Sarah
It is now commonplace to suggest that acts of terrorism on home soil impact the media's ability to challenge the anti-terror policies that follow immediately from them. Still, complex contexts can emerge, and this article focuses on one that shapes a media response to a proposed UK anti-terror policy in 2006. It observes how proposed legislation for an identity card scheme, following closely after the 2005 London bombings, is reported in the elite press according to different 'thresholds'. Emerging from an initial (1) observing of political conflict and a (2) detailing of claims made about the policy are (3) moments of performed criticism of the policy as a 'threat' to the British public's 'civil liberties' by these newspapers. This verbally 'empowered' coverage provides an important exception to the previously observed media passivity in response to anti-terror policies/propaganda. Furthermore, the article argues that this is instigated by a complex context of political contest and reproduced cultural associations that encourage the performance of these newspapers' 'fourth estate' role.